Mythological Characters of the Cultural Space in the Folklore of the Russian North and Norway [Typological Aspects] - Дранникова, Наталья (Poznańskie Studia Slawistyczne, 2012)
Mythological characters of the cultural space in the folklore of the Russian North and Norway (typological aspects)is a comparative analysis of spirits of house that exist in the cultures of both countries. For comparison, we examined different names, habitat, status and functions of spirits at home. For the first time inthe scientific revolution a lot of original folk material is introduced.